Resolving H(Cl, Br, I) capabilities of transforming solution hydrogen-bond and surface-stress - Zhang, Xi (2018)
A combination of differential phonon spectrometrics (DPS) and DFT calculations verified the essentiality of H+ ↔ H+ point fragilization and X− polarization dictating the surface stress of HX (X = Cl, Br, I) solutions. H+ ↔ H+ repulsion breaks the network regularly; X− polarization shortens and stiffens the HO bonds but lengthens and softens the O:H nonbonds in its hydration shell. The X− capability of hydrogen bond and surface stress transformation follows the order of I > Br > Cl. Observations provide fresh insight into the acid solvation network dynamics. DPS resolves solute capabilities of transforming the bonds and surface stress.